2017
DOI: 10.1016/j.bbalip.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Making a membrane on the other side of the wall

Abstract: The outer membrane (OM) of Gram-negative bacteria is positioned at the frontline of the cell’s interaction with its environment and provides a barrier against influx of external toxins while still allowing import of nutrients and excretion of wastes. It is a remarkable asymmetric bilayer with a glycolipid surface-exposed leaflet and a glycerophospholipid inner leaflet. Lipid asymmetry is key to OM barrier function and several different systems actively maintain this lipid asymmetry. All OM components are synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 93 publications
1
35
0
Order By: Relevance
“…1 The outer membrane structure is unique, with an asymmetric lipid bilayer containing Lipopolysaccharide in the outer leaflet. 2 Furthermore, the trans-membrane proteins of the outer membrane are almost exclusively β-barrel in structure, compared to the strictly α-helical nature of proteins found in the inner membrane. Also, unlike most α-helical inner membrane proteins that fold co-translationally, outer membrane proteins (OMPs) fold post-translationally 36 .…”
mentioning
confidence: 99%
“…1 The outer membrane structure is unique, with an asymmetric lipid bilayer containing Lipopolysaccharide in the outer leaflet. 2 Furthermore, the trans-membrane proteins of the outer membrane are almost exclusively β-barrel in structure, compared to the strictly α-helical nature of proteins found in the inner membrane. Also, unlike most α-helical inner membrane proteins that fold co-translationally, outer membrane proteins (OMPs) fold post-translationally 36 .…”
mentioning
confidence: 99%
“…The OM of VBNC cells showed thick, convex patches reminiscent of the flagellar sheath. The asymmetric composition of the OM is tightly regulated to maintain its barrier function (see review [34]). Aberrations, such as the OM patches, might be symptomatic of a perturbed OM maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Intimate structural synergy is now recognized between the peptidoglycan and the teichoic acids of the Gram‐positive bacteria, and between the peptidoglycan and the outer membrane of the Gram‐negative bacteria . Indeed, new opportunities for antibiotic discovery have been identified that interfere with teichoic acid integration into the cell wall of Gram‐positive bacteria and with respect to lipopolysaccharide transport in Gram‐negative bacteria . Within this universe of opportunity, we exemplify our own efforts toward the mechanistic and structural understanding of key enzymes of the bacteria with roles in cell envelope biosynthesis and antibiotic resistance.…”
Section: Cell Envelope‐targeting Antibioticsmentioning
confidence: 99%
“…77,78 Indeed, new opportunities for antibiotic discovery have been identified that interfere with teichoic acid integration into the cell wall of Gram-positive bacteria 69,[79][80][81][82][83][84] and with respect to lipopolysaccharide transport in Gram-negative bacteria. [85][86][87][88][89][90] Within this universe of opportunity, we exemplify our own efforts toward the mechanistic and structural understanding of key enzymes of the bacteria with roles in cell envelope biosynthesis and antibiotic resistance.…”
Section: Cell Envelope-targeting Antibioticsmentioning
confidence: 99%